A Bioactive Constituent of Ginger, 6‐Shogaol, Prevents Adipogenesis and Stimulates Lipolysis in 3T3‐L1 Adipocytes. Issue 1 (18th September 2015) - Suk, Sujin; Seo, Sang Gwon; Yu, Jae Gak; Yang, Hee; Jeong, Eunsun; Jang, Young Jin; Yaghmoor, Soonham Sami; Ahmed, Youssri; Yousef, Jehad Mustafa; Abualnaja, Khalid Omer; Al‐Malki, Abdulrahman Labeed; Kumosani, Taha Abdullah; et al.
Abstract: Z ingiber officinale  Roscoe, one of the most widely used spices, has been reported to have anti‐obesity and anti‐diabetes effects. In the present study, we investigated the effects of 6‐shogaol, a bioactive compound present in ginger, on the adipogenic process in 3T3‐L1 preadipocytes. The anti‐adipogenic effects of 6‐shogaol was significantly higher than the more widely investigated 6‐gingerol, another major ginger constituent. We observed that 6‐shogaol inhibited the expression of two master regulators of adipogenesis, PPARγ and C/EBPα, and also stimulated lipolysis in mature 3T3‐L1 adipocytes. Collectively, these results suggest that 6‐shogaol, not 6‐gingerol, is the major compound present in ginger responsible for its reported anti‐adipogenic properties. Practical Applications: Ginger is widely consumed all over the world, and has been associated with various health benefits. At least some of these benefits have been previously attributed to 6‐gingerol. In the present study, we observed that 6‐shogaol has more potent anti‐adipogenic effects than 6‐gingerol in 3T3‐L1 cells. This is the first study to investigate the anti‐obesity effect of 6‐shogaol in vitro, and provides a new perspective on future development of ginger‐based anti‐obesity strategies.